Organizational consequences of emotional labour in mangenent - Lazányi, Kornélia (Applied Studies in Agribusiness and Commerce, 2011)
Emotional labour, as a self-contained field of research, is only three decades old. This study aims to summarize key findings from investigations of the last ten years in an attempt to provide a reference for interpretation of organizational emotions and the organizational aspects of emotional labour. It makes no secret of its aim being to call the attention of anybody dealing with people as workforce that work no longer has only physical or mental aspects, but an emotional dimension as well. Most often this latter dimension lives an independent life. Normally, it is not regulated, tracked, appreciated or rewarded properly, which might send a message to employees that it is not really important. However, emotional labour is a concomitant of most professions and jobs. Where it is not given any conscious consideration by either the employer nor its employees, numerous opportunities of making it easier or improving it may be lost.